EVALUASI INSTALASI PLUMBING AIR BERSIH PADA GEDUNG SUDIRMAN ROGOJAMPI MENGGUNAKAN PIPE FLOW EXPERT - Hutasoit, Eva Olivia; Hidayat, Taufik (Fakultas Teknik, Universitas Wiraraja, 2024)
The SMK NU Sudirman Rogojampi building has problems with its clean water installation system, namely water distribution that is not smooth and sometimes jammed. This problem is thought to be due to the value of flow speed and pressure in clean water installations that do not meet the applicable minimum requirements. The purpose of this study was to evaluate the installation of clean water in the SMK NU Sudirman Rogojampi building. In this study, the author used the SNI 03-7065-2005 as a reference to calculate the clean water demand and conducted simulations using the Plumbing Pipe Flow Expert software. This software was employed to evaluate and simulate water flow in detail according to the guidelines specified in the SNI 03-7065-2005 related to plumbing systems in buildings. The results of this research indicate that the current clean water demand in the SMK NU Sudirman Rogojampi building is 16,800 liters per day or 16.80 m3 per day. Subsequently, a simulation of the clean water plumbing installation was performed using the Pipe Flow Expert software. In the first simulation, the generated water flow rate was in accordance with the field testing results, and the flow velocity only met the minimum requirements of SNI 03-7065-2005 for pipes numbered 1, 2, 12, 14, 18, 20, and 21. The water pressure also met the minimum requirements at nodes 5 and 24. In the second simulation, the results showed that the water flow rate, flow velocity, and pressure in the installation met the minimum requirements specified in SNI 03-7065-2005. Based on the simulation results, a suitable simulation was obtained, namely in the second simulation in the form of an improvement in the addition of an upper pusher pump from the rooftank to increase the speed and pressure of water in the clean water installation of the SMK NU Sudirman Rogojampi building.